Analysis of the temporal variability of CO2, CH4 and CO concentrations at Lamto, West Africa. Issue 1 (1st January 2021) - Tiemoko, Toure Dro; Ramonet, Michel; Yoroba, Fidele; Kouassi, Kobenan Benjamin; Kouadio, Kouakou; Kazan, Victor; Kaiser, Claire; Truong, François; Vuillemin, Cyrille; Delmotte, Marc; Wastine, Benoit; Ciais, Phillipe
Abstract: The 10-year observations of the atmospheric molar fractions of CO2, CH4 and CO in West Africa were analyzed using a high precision measurement of the Lamto (LTO) station (6°31 N and 5°02 W) in Côte d'Ivoire. At daily scale, high concentrations appear at night with significant peaks around 7 a.m. local time and minimum concentrations in the afternoon for CO2 and CH4 . The CO concentrations show two peaks around 8 h and 20 h corresponding to the maximum in road traffic of a northern motorway located 14 km from the station. The long-term increase rates of CH4 (∼7 ppb year −1 ) and CO2 (∼2.24 ppm year −1 ) at Lamto are very close to global trends. The variations of the concentrations of the three gases show strong seasonality with a peak in January for all gases and minima in September for CO2 and CH4, and in June for CO. The CO variation suggests a significant impact of fires on the CO, CO2 and CH4 anomalies in the Lamto region during the dry season (December to February). CO and CH4 show strong correlations (at synoptic-scale and monthly based) in January ( r =  0.84), February ( r =  0.90), April ( r =  0.74), November ( r =  0.79) and December ( r =  0.72) reflecting similar sources of emission for both gases. The trajectories of polluted air masses at LTO, also indicate continental sources of emission associated with Harmattan winds.